Selected coastal engineering papers of Robert L. Wiegel - 270107 Wiegel, Robert L.; Edge, Billy L. 418684; Coasts, Oceans, Ports and Rivers Institute (American Society of Civil Engineers) 519005; American Society of Civil Engineers. 6189 (Reston, Va. : American Society of Civil Engineers)
Includes bibliographical references and index.